Intrusion Detection Systems Based on Artificial Intelligence Techniques in Wireless Sensor Networks - Nabil Ali Alrajeh; J. Lloret (International Journal of Distributed Sensor Networks)
Intrusion detection system (IDS) is regarded as the second line of defense against network anomalies and threats. IDS plays an important role in network security. There are many techniques which are used to design IDSs for specific scenario and applications. Artificial intelligence techniques are widely used for threats detection. This paper presents a critical study on genetic algorithm, artificial immune, and artificial neural network (ANN) based IDSs techniques used in wireless sensor network (WSN).